Implementation of Community Based Tourism in the Development of Kampung Lawas Maspati in Surabaya City - Zahrotul Ulya, Chorida Maulidil; Casmiwati, Dewi (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Kampung Lawas Maspati, which is located on Jl. Maspati, Bubutan District, Surabaya City has many achievements. Kampung Lawas Maspati also has a historical icon and local wisdom that is still maintained. The people of Kampung Lawas Maspati implement a community based tourism destination. The purpose of this study is to describe and analyze the application of community-based tourism of Kampung Lawas Maspati in Surabaya City. The research method used is descriptive with a qualitative approach. The theory uses the Community Based Tourism (CBT) theory according to Suansri. The results of this study show that the application of community-based tourism in the development of Kampung Lawas Maspati is still not successful, because there is still no regeneration in managing Kampung Lawas Maspati into a tourist village. Kampung Lawas Maspati has been good and has become an independent and more developed Village. Beside that, the community benefits from the development of Kampung Lawas Maspati, Surabaya.